Widespread dominance of methane ebullition over diffusion in freshwater aquaculture ponds - Vroom, Renske J. E.; Kosten, Sarian; Almeida, Rafael M.; Mendonça, Raquel; Muzitano, Ive S.; Barbosa, Icaro; Nasário, Jonas; Oliveira Junior, Ernandes S.; Flecker, Alexander S.; Barros, Nathan (Frontiers in Water, 2023)
This is a provisional file, not the final typeset article An ever-increasing demand for protein-rich food sources combined with dwindling wild fish stocks has caused the aquaculture sector to boom in the last two decades. Although fishponds are potentially strong emitters of the greenhouse gas methane (CH4), little is known about the magnitude, pathways, and drivers of these emissions. We measured diffusive CH4 emissions at the margin and in the center of 52 freshwater fishponds in Brazil. In a subset of ponds (n=31) we additionally quantified ebullitive CH4 fluxes and sampled water and sediment for biogeochemical analyses. Sediments (n=20) were incubated to quantify potential CH4 production. Ebullitive CH4 emissions ranged between 0 and 477 mg m -2 d -1 and contributed substantially (median 85%) to total CH4 emissions, surpassing diffusive emissions in 81% of ponds. Diffusive CH4 emissions were higher in the center (median 11.4 mg CH4 m -2 d -1 ) than at the margin (median 6.1 mg CH4 m -2 d -1 ) in 90% of ponds. Sediment CH4 production ranged between 0 and 3.17 mg CH4 g C -1 d -1 . We found no relation between sediment CH4 production and in situ emissions. Our findings suggest that dominance of CH4 ebullition over diffusion is widespread across aquaculture ponds. Management practices to minimize the carbon footprint of aquaculture production should focus on reducing sediment accumulation and CH4 ebullition.